The influence of palm kernel cake on small intestine and ceca microflora population of Cherry Valley duck - Mohd Nor, Noor Amirah (2015)
Palm kernel cake (PKC) is a by-product of the cultivation of oil palm trees (Elaeisguineesis Jacq.). Approximately, 85% of the world’s palm oil are produced by Indonesia and Malaysia. In Malaysia, oil palm plantations make up 77% of agricultural land or about 15% of total land area. During 2013, Malaysia have been produced 2 516 664 tonnes of PKC. Large amount of PKC been produced and consistently available with reasonable price are the reasons to use this agricultural by-product to partially substitute the commercial animal feed especially in poultry industry. However, in poultry industry, the used of PKC as animal feed is rather limited because of high level of fibre in the PKC and low digestibility of palm kernel cake. A study was conducted to investigate the effects of PKC supplementation on small intestinal bacterial population and villi height in Cherry Valley duck. Thirty six four-days-old Cherry Valley male ducks were randomly assigned into 9 cages based on simple random sampling. Three dietary treatments were used with three replicate per treatment and four ducks per replicates for Treatment 1 (T1), Treatment 2 (T2) and Treatment 3 (T3). Treatment 1 was kept as control and received basal diet while T2 and T3 were treated with basal diet with inclusion of 15% PKC and 35% PKC respectively. The ducks were raised for two months before slaughter for sample collection. There were significant different (P<0.05) for total bacteria population in T2 when compare to T1. Supplementation of 35% PKC in T3 result in significantly increased of Lactobacilli sp. colony as compared to T1. The number of Escherichia coli formed in T2 and T3 were reduced as compared to T1. However, only T2 show significant reduction in Escherichia coli colony formed. The number of Coliform were significantly reduced in T2 and T3 as compared to T1. For the villus height and crypt depth of ileum, the study shows that there are no significant different (P>0.05) for Treatment 2 and Treatment 3 as compared to Treatment 1. From this study, it can be concluded that increased dietary fibre content might be expected to increase the total numbers of bacteria and alter the makeup of the microflora in the intestinal tract. However, different level of PKC inclusion in diet do not affect the villus height and crypt depth of the ileum.